2021
DOI: 10.1071/cp21206
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of grain micronutrient concentrations and grain yield components in a doubled haploid bread wheat (

Abstract: Bread wheat (Triticum aestivum L.) is an important cereal crop that provides >20% of the global calorie intake. Bread wheat contains micronutrients, and thus plays a significant role in nutritional and food securities especially in developing countries. However, its grains are inherently deficient in some micronutrients, particularly iron and zinc, which makes them important biofortification targets. Our objective was to investigate variations in micronutrients and their relationship with grain yield co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Wheat is a cereal crop which accounts for one-fifth of the calories consumed by humans all over the world [ 4 , 19 ]. The wheat kernel ( Figure 1 ) is made up of three components: (i) the endosperm, which constitutes about 80–85% of the kernel and is rich in protein and starch), and (ii) the germ (or embryo), which makes up about 2–3% of the kernel and is rich in protein, fat, vitamins and (iii) the bran, which constitutes about 13–17% of the kernel and rich in fibre.…”
Section: Flourmentioning
confidence: 99%
See 2 more Smart Citations
“…Wheat is a cereal crop which accounts for one-fifth of the calories consumed by humans all over the world [ 4 , 19 ]. The wheat kernel ( Figure 1 ) is made up of three components: (i) the endosperm, which constitutes about 80–85% of the kernel and is rich in protein and starch), and (ii) the germ (or embryo), which makes up about 2–3% of the kernel and is rich in protein, fat, vitamins and (iii) the bran, which constitutes about 13–17% of the kernel and rich in fibre.…”
Section: Flourmentioning
confidence: 99%
“…The starch granules are generally closely packed in the protein matrix and adherence between starch and protein is usually strong in hard wheat. Most hard wheat varieties are known to contain a higher amount of protein than do most soft wheat flours but protein concentration does not necessarily depend on hardness as it differs remarkably within a class and even within a given cultivar [ 19 ]. With respect to the gluten content, wheat flour is categorized as “soft” or “weak” if the gluten content is low (7–12%) and “hard” or “strong” when the gluten content is high (12–18%).…”
Section: Flourmentioning
confidence: 99%
See 1 more Smart Citation
“…Tahir et al (2022) evaluated advanced breeding lines of wheat for genes related to Zn and Fe concentrations in grains. From a population of doubled haploid lines of wheat, Lephuthing et al (2022) identified 15 lines (high in Fe, Zn and yield) for future research. Regarding selection of lowantinutrient genotypes, Ragi et al (2022) identified several promising maize hybrids produced from inbred lines of wildtype and subtropically adapted low-phytate mutants (lpa1-1).…”
Section: Genetic Biofortificationmentioning
confidence: 99%
“…Wheat production is essential for global food security, providing over 20% of the world's total calorie intake (Lephuthing et al 2021). High-producing and exporting regions are especially important, northern Kazakhstan being one of them.…”
Section: Introductionmentioning
confidence: 99%